Counterproductive : Time Management in the Knowledge Economy - Gregg, Melissa, 1978- (Book collections on Project MUSE., 2018)
As online distractions increasingly colonize our time, why has productivity become such a vital demonstration of personal and professional competence? When corporate profits are soaring but worker salaries remain stagnant, how does technology exacerbate the demand for ever greater productivity? In Counterproductive Melissa Gregg explores how productivity emerged as a way of thinking about job performance at the turn of the last century and why it remains prominent in the different work worlds of today. Examining historical and archival material alongside popular self-help genres--from housekeeping manuals to bootstrapping business gurus, and the growing interest in productivity and mindfulness software--Gregg shows how a focus on productivity isolates workers from one another and erases their collective efforts to define work limits. Questioning our faith in productivity as the ultimate measure of success, Gregg's novel analysis conveys the futility, pointlessness, and danger of seeking time management as a salve for the always-on workplace. -- Provided by publisher.